Baryons and antibaryons in compressed nuclear matter - Gaitanos, Theodoros; Chorozidou, Arsenia (HNPS Advances in Nuclear Physics, 2023)
In this work we discuss the in-medium properties of baryons and antibaryons in nuclear matter at densities beyond saturation. We focus the attention on the in-medium optical potentials of heavy baryons with strangeness content. That is, the hyperons Λ, Σ with strangeness S=-1 and the cascade particle Ξ with S=-2 . The particular treatment of the hyperons inside compressed matter is crucial in order to understand the in-medium modifications of baryons in matter conditions that may occur in the interior of neutron stars. We dicsuss further the properties of their antiparticles, since there are experimental data for the nucleonic sector (S=0) while for the strangeness sector (S=-1,-2) experimental information will be available in the close future at the new facilities, for instance, at FAIR and J-PARC.